2022
DOI: 10.3390/nu14040741
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Stimulation by Fennel (Foeniculum vulgare Mill.) Essential Oil Improves Lipid Metabolism and Metabolic Disorders in High Fat-Induced Obese Rats

Abstract: In this study, odor components were analyzed using gas chromatography/mass spectrometry (GC/MS) and solid-phase microextraction (SPME), and odor-active compounds (OACs) were identified using GC-olfactometry (GC-O). Among the volatile compounds identified through GC-O, p-anisaldehyde, limonene, estragole, anethole, and trans-anethole elicit the fennel odor. In particular, trans-anethole showed the highest odor intensity and content. Changes in body weight during the experimental period showed decreasing values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
4
2
2
Order By: Relevance
“…According to the obtained results from this Parameters Groups study, it is concluded that Fennel 10% have the best effect in glucose lowering activity. These findings are comparable to Hong et al, (2022) who estimated the olfactory stimulation by fennel (Foeniculum vulgare, Mill) essential oil improves lipid metabolism and metabolic disorders in high fat-induced obese rats.…”
Section: Glucose Contentsupporting
confidence: 87%
See 2 more Smart Citations
“…According to the obtained results from this Parameters Groups study, it is concluded that Fennel 10% have the best effect in glucose lowering activity. These findings are comparable to Hong et al, (2022) who estimated the olfactory stimulation by fennel (Foeniculum vulgare, Mill) essential oil improves lipid metabolism and metabolic disorders in high fat-induced obese rats.…”
Section: Glucose Contentsupporting
confidence: 87%
“…The obtained results are comparable to El Rabey et al, (2013) who demonstrated that the mean values of serum triglycerides (s.TG) in the positive control 114.26 ± 1.67 mg/dL was significantly (𝑃𝑃≤0.001) higher than that of the negative control 93.34 ± 5.7 mg/dL (In the barley treated group, the mean values of the s.TG 62.06 ± 6.44 mg/dL was reduced significantly as compared to the positive control group 114.26 ± 1.67 mg/dL. The findings are compatible to Hong et al, (2022) they demonstrated that the TG level showed a significant increase in the positive control group 102.52 ± 3.14mg/dl as compared to the normal control group 94.20 ± 3.03 mg/dl. In addition, the TG level was decreased in the fennel seeds treated group 88.75 ± 2.02 mg/dl as compared to the positive control group 102.52 ± 3.14 mg/dl after 7 weeks of treatment.…”
Section: Serum Lipid Profilessupporting
confidence: 77%
See 1 more Smart Citation
“…When fennel oil and CPZ were administered concurrently, the ACTH and cortisol levels in the sera were preserved. The precise mechanism of how the active ingredients of fennel oil affect plasma cortisol is still unknown (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Stems and leaves were very rich in α-phellandrene (36.85% and 41.59%, respectively) and β-phellandrene (19.68% and 25.79%, respectively), whereas the main components of fruits were terpinolene (20.10%) and limonene (17.84%). Also, Hong et al [ 73 ] indicated that trans -anethole and fenchone had the highest and second-highest concentrations among fennel essential oil volatiles. To our knowledge, there has been no research on the bio-changes that occur in phyto-constitutes and volatiles during FS sprouting.…”
Section: Discussionmentioning
confidence: 99%